Good Corporate Governance, Ukuran Perusahaan, Nilai Perusahaan dan Profitabilitas sebagai Variabel Moderasi - Nugraheni, Ni Putu Tara Asti; Suaryana, I Gustu Ngurah Agung (E-Jurnal Akuntansi; Vol 34 No 6 (2024)DO - 10.24843/EJA.2024.v34.i06.p12, 2024)
This study aims to obtain empirical evidence regarding the influence of good corporate governance, and firm size on firm value with profitability as a moderating variable. This research was conducted on consumer non-cyclicals sector companies on the Indonesia Stock Exchange in the period 2017 – 2021. The sampling method was purposive sampling, and a sample was 58 companies with 290 observations. The data analysis technique used is Moderated Regression Analysis (MRA). Based on the research results obtained, good corporate governance has a significant positive effect on firm value, firm size has no effect on firm value, profitability can moderate the effect of good corporate governance on firm value, and profitability is not able to moderate the effect of firm size on firm value. Keywords: Good Corporate Governance; Firm Size; Profitability; Firm Value